2013
DOI: 10.5603/cj.2013.0100
|View full text |Cite
|
Sign up to set email alerts
|

Whether noninvasive optimization of AV and VV delays improves the response to cardiac resynchronization therapy

Abstract: (Cardiol J 2013; 20, 4: 411-417)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…25) Combining optimized AVDs/ VVDs provided the best hemodynamic response. 26) Problems of AVD/VVD optimization with UCG: Choosing a method for AVD/VVD optimization is a crucial matter. UCG is the most widely used method; however, one study demonstrated that the optimization of AVD and IMPEDANCE CARDIOGRAPHY FOR CRT OPTIMIZATION VVD with UCG failed to significantly improve SV.…”
Section: 54)mentioning
confidence: 99%
“…25) Combining optimized AVDs/ VVDs provided the best hemodynamic response. 26) Problems of AVD/VVD optimization with UCG: Choosing a method for AVD/VVD optimization is a crucial matter. UCG is the most widely used method; however, one study demonstrated that the optimization of AVD and IMPEDANCE CARDIOGRAPHY FOR CRT OPTIMIZATION VVD with UCG failed to significantly improve SV.…”
Section: 54)mentioning
confidence: 99%
“…Unlike in recent years, optimization of the therapy is performed a few weeks after implantation, using simple echocardiographic measurements, since the atrioventricular and interventricular intervals may be different in each individual and change over time. Several studies [55][56][57] show improved cardiac failure data and even improved survival in patients with scheduled post-implant visits. At these visits, problems can be detected with early correction and improvement of the prognosis of these patients (malignant ventricular arrhythmias, atrial fibrillation, ventricular pacing time of less than 90-95%, diaphragmatic pacing, inadequate electrode pacing, etc.).…”
Section: Optimization Of Resynchronization Therapymentioning
confidence: 99%